Muscle-Tendon Unit Properties during Eccentric Exercise Correlate with the Creatine Kinase Response - Hicks, Kirsty M.; Onambele-Pearson, Gladys L.; Winwood, Keith; Morse, Christopher I. (Frontiers in Physiology, 2017)
Aim: The aim of this paper was to determine whether; 1) patella tendon stiffness, 2) the magnitude of vastus lateralis fascicle lengthening, and 3) eccentric torque correlate with markers of exercise induced muscle damage. Method: Combining dynamometry and ultrasonography, patella tendon properties and vastus lateralis architectural properties were measured pre and during the first of six sets of 12 maximal voluntary eccentric knee extensions. Maximal isometric torque loss and creatine kinase activity were measured pre-damage (-48 hrs), 48, 96 and 168 hrs post-damage as markers of exercise-induced muscle damage. Results: A significant increase in creatine kinase (883 ± 667 UL) and a significant reduction in maximal isometric torque loss (21%) was reported post-eccentric contractions. Change in creatine kinase from pre to peak significantly correlated with the relative change in vastus lateralis fascicle length during eccentric contractions (r = 0.53, p = 0.02) and with eccentric torque (r = 0.50, p = 0.02). Additionally, creatine kinase tended to correlate with estimated patella tendon lengthening during eccentric contractions (p < 0.10). However, creatine kinase did not correlate with resting measures of patella tendon properties or vastus lateralis properties. Similarly, torque loss did not correlate with any patella tendon or vastus lateralis properties at rest or during eccentric contractions. Conclusion: The current study demonstrates that the extent of fascicle strain during eccentric contractions correlates with the magnitude of the creatine kinase response. Although at rest, there is no relationship between patella tendon properties and markers of muscle damage; during eccentric contractions however, the patella tendon may play a role in the creatine kinase response following EIMD.